New epoxy anchor for better bonding between FRP sheets and concrete - Yuan, C.; Chen, Wensu; Pham, Thong; Hao, Hong; Chen, L.; Zhang, M. (ELSEVIER SCI LTD, 2020)
This study carried out an experimental investigation on the effectiveness of newly proposed epoxy anchors on the interfacial bond performance between basalt fibre reinforced polymer (BFRP) sheets and concrete. The parameters examined included the size of epoxy anchors and the number and spacing of anchors. It is concluded that the proposed epoxy anchors remarkably enhanced the shear resistance while the progressive FRP debonding was significantly postponed. The experimental results showed an average 77.49% increment in the bond strength, 86.71% increment in the utilization of BFRP sheets, and 78.10% increase in the peak shear stress. A bond strength model by incorporating the effects of strain energy and bonding area of epoxy resin was proposed to analyse the effect of anchorage. The predicted debonding load showed good agreement with the testing data.